Digital Fashion: A systematic literature review. A perspective on marketing and communication. Issue 1 (2nd January 2021) - Noris, Alice; Nobile, Tekila Harley; Kalbaska, Nadzeya; Cantoni, Lorenzo
ABSTRACT: Research in the overlapping area between Fashion and Information and Communication Technologies – hereafter referred to as "Digital Fashion" – is growing and attracting the interest of both academics and practitioners. However, due to the richness and heterogeneity of the involved fields, no map is already available of it. A systematic literature review was conducted in July 2019 utilizing the keywords "digital" and "fashion" in five research databases, including academic papers from 1998. This provided 491 relevant items for analysis. Three main categories to which those research papers belong to are identified: (i) Communication and Marketing (C&M) ; (ii) Design and Production (D&P) ; and (iii) Culture and Society (C&S) . Each category includes two or three subcategories. This study provides an overview of the state of the art of digital fashion studies, with a focus on Communication and Marketing related research.